Kontribusi Energi Hijau terhadap Bio-Ekonomi: Analisis Aspek Finansial dan Lingkungan - Cut Rusmina; Syaifuddin Yana; Khairuna; Ulfia; Rahmi; Nelly (Faculty of Engineering, Universitas Serambi Mekkah, 2024)
This article examines green energy’s financial and environmental impact on the bio-economy. Renewable energy sources like solar, wind, and biomass can address climate change and fossil fuel dependence. This article uses literature analysis, case studies of green energy implementation in various nations, and empirical data on green energy’s financial and environmental implications. Long-term operational cost savings from green energy technology investments and their investment potential and economic advantages. Other benefits of renewable energy include lowering greenhouse gas emissions and improving air quality. The long-term implications of green energy adoption on the bio-economy are unknown, and more research is needed to determine the best strategies to promote green energy adoption. Thus, this review on green energy, bi-economics, and financial and environmental analysis should be instructive. This study should reveal how green energy can boost the bio-economy and solve global economic and environmental issues. This study should also improve policy suggestions and implementation tactics to optimize green energy advantages within a bio-economic framework.